O prawo do różnicy – o postawie zaangażowanej w pisarstwie Predraga Matvejevicia (szkic) - Kubik, Damian (Slavia Occidentalis, 2016)
The article attempts to analyse the concept of engagement (commitment) in the books of Predrag Matvejević, a remarkable Croatian intellectual. Starting with a short presentation of his nonconformist views on political, social and cultural issues, the article focuses on highlighting the main features of his fight for the right to be different, one of the most important rights in the eyes of an intellectual.